1990
DOI: 10.1007/bf00195250
|View full text |Cite
|
Sign up to set email alerts
|

Graded cytopathogenicity of the human immunodeficiency virus (HIV) in the course of HIV infection

Abstract: To determine whether the biological variability of HIV-1 has any clinical significance, the highly variable cytopathogenicity of 153 HIV-1 strains, isolated from 119 hemophiliacs, was related to the number of CD4+ lymphocytes present in the patient's blood at the time of virus isolation. It was shown that the cytopathogenicity of the HIV-1 isolates was inversely correlated with the number of CD4+ lymphocytes. The highest CD4+ cell number were observed in 34 latently infected patients characterized by HIV serop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Assuming dose proportionalities, the oral bioavailabilities for HBY 097 and S-2720 were calculated from the area under the data values for intravenous and oral administration. When compared with S-2720, HBY AZT resistant (n ϭ 14 a AZT-resistant strains either had at least one of the five known resistanceconferring mutations (13,20) in the RT gene or the IC 90 of AZT for the strains was Ͼ1.5 M. Differentiation of SI and NSI viruses was done as described previously (36). 097 achieved a considerably higher degree of oral absorption (48 versus 10%).…”
Section: Resultsmentioning
confidence: 99%
“…Assuming dose proportionalities, the oral bioavailabilities for HBY 097 and S-2720 were calculated from the area under the data values for intravenous and oral administration. When compared with S-2720, HBY AZT resistant (n ϭ 14 a AZT-resistant strains either had at least one of the five known resistanceconferring mutations (13,20) in the RT gene or the IC 90 of AZT for the strains was Ͼ1.5 M. Differentiation of SI and NSI viruses was done as described previously (36). 097 achieved a considerably higher degree of oral absorption (48 versus 10%).…”
Section: Resultsmentioning
confidence: 99%
“…1 B of HIV-1 seropositive individuals representing either low or high cytopathic HIV-1 strains. The cytopathic effects of the viruses isolated from the patients were examined in vitro [26]. We could not find any linkage between the detection of Nef antibodies and the in vitro virus pathogenicity (data not shown).…”
mentioning
confidence: 93%
“…For a majority of these patients, these findings were constant over several years, whereas in a minority of patients, a development from culture negative to the SI phenotype with an intermediate NSI stage was observed [Witt et al, 1996]. Previous studies have shown a good correlation of the HIV phenotype with the CD4+ T-cell count [Schneweis et al, 1990;Koot et al, 1993a;Fouchier et al, 1995;Koot et al, 1996] and with progression to AIDS [Koot et al, 1993b;Richman et al, 1994].…”
Section: Introductionmentioning
confidence: 73%